EFISIENSI PENGGUNAN MODAL, TENAGA KERJA, DAN BAHAN BAKU TERHADAP PRODUKSI INDUSTRI KERAJINAN PERAK DI GIANYAR - Semita, I Putu Rama Pramana; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 9 (2021): VOL 10 NO 9, SEPTEMBER 2021 [3528 - 3965], 2021)
Economic growth can be influenced by the scale of production produced if the scale of production produced continues to increase, the impact on the level of efficiency of the use of production factors such as capital, labor, and raw materials also increases. The purpose of this study is to determine the effect of capital, labor, and raw materials on production and to determine the level of efficiency and scale of production produced. The data used are primary data, namely by distributing questionnaires in each silver handicraft industry in Celuk Village, Gianyar Regency. The sample used was 40 business units of the silver handicraft industry in Celuk Village, Gianyar Regency. The sampling technique is saturated sampling. Using multiple linear regression analysis techniques in the form of double log. The results showed that capital, labor, and raw materials simultaneously had a significant influence on production. Capital, labor and raw materials have a partially significant effect on production, the level of efficiency of capital, labor, and efficient raw materials and the scale of production in the Scale of Return to Scale. The variable that has the most influence on production is capital.   Keywords: Capital, Labor, Raw Materials, and Production